Komunikasi pustakawan dalam menciptakan kenyamanan dan membangun kepercayaan di perpustakaan SMP IT Al Binaa - Nasution, Nona Astri; Rusmana, Agus; Rodiah, Saleha (Universitas Negeri Malang, 2025)
Librarians’ communication for fostering comfort and trust in the Al Binaa Islamic Junior High School library This study aims to examine the role of interpersonal communication by librarians in improving library accreditation at SMP IT Al Binaa, Bekasi Regency. The research focuses on identifying the factors influencing the effectiveness of communication between librarians and library stakeholders, including students, teachers, and school staff, in enhancing the library’s overall performance and accreditation status. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The results highlight that effective interpersonal communication, characterized by trust, clarity, and empathy, significantly improves library services, fosters collaboration, and supports accreditation processes. Additionally, the study found that librarians' ability to engage with diverse stakeholders and address their needs plays a critical role in the library’s success in meeting accreditation standards. This research provides valuable insights for educational institutions seeking to enhance library services and accreditation through effective communication strategies. Penelitian ini bertujuan untuk memeriksa peran komunikasi interpersonal oleh pustakawan dalam meningkatkan akreditasi perpustakaan di SMP IT Al Binaa, Kabupaten Bekasi. Penelitian ini berfokus pada identifikasi faktor-faktor yang mempengaruhi efektivitas komunikasi antara pustakawan dan pemangku kepentingan perpustakaan, termasuk siswa, guru, dan staf sekolah, dalam meningkatkan kinerja keseluruhan perpustakaan dan status akreditasi. Menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara, pengamatan, dan analisis dokumen. Hasilnya menyoroti bahwa komunikasi interpersonal yang efektif, ditandai dengan kepercayaan, kejelasan, dan empati, secara signifikan berkontribusi untuk meningkatkan layanan perpustakaan, mendorong kolaborasi, dan mendukung proses akreditasi. Selain itu, penelitian menemukan bahwa kemampuan pustakawan untuk terlibat dengan beragam pemangku kepentingan dan memenuhi kebutuhan mereka memainkan peran penting dalam keberhasilan perpustakaan dalam memenuhi standar akreditasi. Penelitian ini memberikan wawasan berharga bagi institusi pendidikan yang ingin meningkatkan layanan perpustakaan dan akreditasi melalui strategi komunikasi yang efektif.